Transient spectroscopic characterization and theoretical modeling of fulvic acid radicals formed by UV-A radiation - Martin, Marcela Vanessa (2017)
Laser flash-photolysis experiments (λexc = 355 nm) performed with aqueous solutions of Pony Lake and Waskish Peat fulvic acids at pH = 2 showed formation of transient species with absorption maxima at 470?480 nm with O2-independent lifetimes of 600?700 μs, which were assigned to a phenoxyl radicals. Formation of these radicals occurs after photoionization of the fulvic acids followed by fast deprotonation process. Photoacoustic experiments at the same excitation wavelength yielded the O2-independent fraction of energy stored at times longer than 135 ns. DFT calculations were performed to estimate the absorption spectra and energy content of the phenoxyl radicals and triplet excited state of the Buffle´s model of the fulvic acid. Combination of the DFT and photoacoustic data yielded the photoionization quantum yields of both FA, which were compared to reported values obtained by steady-state and time-resolved techniques.